FACTORS THAT INFLUENCE ORAL HEALTH BEHAVIORS IN YOUNG ADULTS - Adina Oana Armencia; Andrei Nicolau; Anca Rapis; Irina Bamboi; Ramona Feier; Cristian Romanec; Alex Călin; Roșu Leata Gabriela; Carina Balcoș (Romanian Dental Association for Education, 2023)
Changing old habits and adopting new behaviors can be challenging and requires perseverance and motivation. For this reason, the study aimed to determine oral health behaviors among young adults. MATERIALS AND METHODS: The study group consisted of 129 students from "Grigore T. Popa" University in Iași, during the period of February 2023 to March 2023. The questionnaire method was used, specifically the Health-Promoting Lifestyle Profile II - HPLP II and the Generalized Self-Efficacy Scale. RESULTS: The students showed a moderate tendency to change in almost all areas assessed by the HPLP II questionnaire. For the "interpersonal relationships" domain, the average score of 2.74 indicated a strong desire for change. The GSE score α is 28.47, indicating a moderate to high confidence in dealing with challenging situations. CONCLUSIONS: The message of promoting health-promoting behavior is perceived positively, thus reducing behavioral barriers and promoting the prompt adoption of correct behavior.